Pemodelan Sistem Pakar Diagnosis Penyakit Tanaman Apel Manalagi Dengan Metode Backward Chaining Menggunakan Certainty Factor - Muhammad Burhannudin; Suprapto Suprapto; Nurul Hidayat (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Kota Batu is one Agropolitan city located in East Java province with huge potential for development in agriculture. Apple is a fruit plant that can live well in the highlands. This plant in Indonesia since 1934. As other fruit crops, apples are also susceptible to the disease. Maintaining plants from disease is also an attempt to preserve the environment. One form of such vandalism is negligence of farmers in preserving plants from disease. Making this system an attempt to perform human roles. This system is expected to help farmers, in particular, to be able to identify precisely the apple crop diseases and appropriate. So can meminimalisi impact. This application is developed using PHP programming language and MySQL database. Both are a combination of the most popular in the manufacture of web-based applications. While the inference method used is Backward chaining which is based on the tracking of data or facts then led to the conclusion in the form of conclusions pests or diseases that attack the apple crop. Tests performed by comparing the suitability of the output with the diagnosis expert system. And of the 30 test cases the data obtained accuracy rate modeling expert system testing using methods Certainty Factor on apple crop disease diagnosis system amounted to 93.3%. With the accuracy of the results indicate that the system is able to replace the role of experts.